De léxico diplomático: nomenclaturtas del documento medieval en el occidente peninsular (siglos VIII-XII) - Martín López, María Encarnación (Estudios humanísticos. Geografía, historia y arte, 1991)
One of the problems raised in dealing with a document as an ordinary source is that of its own nomenclature. The present paper resumes such questions, and gathers and analyses the main terms used in the medieval documentation of León and Castile, as well as their evolution and cultural connotations.